Dynamics of viral DNA shedding and culture viral DNA positivity in different clinical samples collected during the 2022 mpox outbreak in Lombardy, Italy - Piralla, Antonio; Mileto, Davide; Rizzo, Alberto; Ferrari, Guglielmo; Giardina, Federica; Gaiarsa, Stefano; Petazzoni, Greta; Bianchi, Micol; Salari, Federica; Bracchitta, Fiorenza; Sammartino, Josè Camilla; Ferrari, Alessandro; et al. (Travel medicine and infectious disease, 2024)
Mpox virus (MPXV) has recently spread outside of sub-Saharan Africa. This large multicentre study was conducted in Lombardy, the most densely populated Italian region accounting for more than 40% of Italian cases. The present study aims to: i) evaluate the presence and the shedding duration of MPXV DNA in different body compartments correlating the MPXV viability with the time to onset of symptoms; ii) provide evidence of MPXV persistence in different body compartment as a source of infection and iii) characterize the MPXV evolution by whole genome sequencing (WGS) during the outbreak occurred in Italy. The study included 353 patients with a laboratory-confirmed diagnosis of MPXV infection screened in several clinical specimens in the period May 24th - September 1st, 2022. Viral isolation was attempted from different biological matrices and complete genome sequencing was performed for 61 MPXV strains. MPXV DNA detection was more frequent in the skin (94.4%) with the longest median time of viral clearance (16 days). The actively-replicating virus in cell culture was obtained for 123/377 (32.6%) samples with a significant higher viral quantity on isolation positive samples (20 vs 31, p < 0.001). The phylogenetic analysis highlighted the high genetic identity of the MPXV strains collected, both globally and within the Lombardy region. Skin lesion is gold standard material and the high viral load and the actively-replicating virus observed in genital sites confirms that sexual contact plays a key role in the viral transmission. •MPXV detection was more frequent from the skin lesions (289 of 306, 94·4%).•The median clearance time of MPXV DNA was 16 days in the skin, 14 days in the oropharynx.•Higher isolation rate was observed in semen, urine, anogenital, urethral and skin samples.•Higher isolation rate was observed in samples collected between 0 and 7 days (65/158, 41.1%) from the onset of symptoms.•Our 61 genomes are distributed in 37 local subclusters of the outbreak clade.